Evaluation of morphometric parameters of Puincha micro watershed – A remote sensing and GIS approach - ROUT, P. K.; PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2021)
In the present study, evaluation of various morphometric parameters has been carried out using remote sensing (RS) and geographical information system (GIS) techniques to access the geo-hydrological characteristics of Puincha micro-watershed of Odisha. The drainage networks of Puincha were delineated using IRS-1D-LISS-III-FCC data merged satellite data on 1:50,000 scale. Survey of India (SOI) toposheets were used as reference with limited field work. Evaluation of morphometric parameters in respect of linear, aerial and relief aspects of the micro watershed were calculated using various techniques. Various morphometric parameters like stream order, stream length, bifurcation ratio, drainage density, stream frequency, form factor, texture ratio, relief ratio, relative relief, circulatory ratio, elongation ratio etc were worked out for the watershed and discussed in this paper. The value of form factor of the watershed is obtained as 0.427 which reveals that the watershed is elongated and flat in nature. Drainage density is found to be 0.067 km-1 which indicates extremely low drainage density nature of the micro watershed. The bifurcation ratio is found to be 1.85 which shows that the watershed has less structural disturbances and the drainage pattern is distorted. The study further reveals that RS and GIS are the potential tool for morphometric study.